The staging of discrimination (Revista Rupturas, 2016)
The aim of this article is to share the perceptions of inequality that Costa Rican women artists experience. In Costa Rica's art history, women appear as founders/formers of the first academies of ballet and dance, prominence that makes it even more urgent to unveil the transformation processes, levels of perception (as generations of the artists) and discover their concerns regarding possible signs of power and invisibility. The analysis is constructed from interviews. This article is the first window to look and question whether dominance and patriarchy have their own ways in the world of art is already an achievement, while shows the participation and the career of women artists.